2012
DOI: 10.1007/s00464-012-2529-4
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic simulation training: does timing impact the quality of skills acquisition?

Abstract: All subjects improved in skill significantly throughout the week regardless of the timing of the training intervention. Simulation training can be offered outside of regular working hours with acceptable effectiveness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“… 6 Using an online booking system, residents could book 2-hour training sessions at the simulation center during the daytime, or the evening, throughout the week, including weekends. 7 There was sufficient equipment for 4 residents to practice simultaneously (4 virtual reality simulators and 4 box trainers). Medical students attended all training sessions, to assist with technical problems and provide feedback and instructions.…”
Section: Methodsmentioning
confidence: 99%
“… 6 Using an online booking system, residents could book 2-hour training sessions at the simulation center during the daytime, or the evening, throughout the week, including weekends. 7 There was sufficient equipment for 4 residents to practice simultaneously (4 virtual reality simulators and 4 box trainers). Medical students attended all training sessions, to assist with technical problems and provide feedback and instructions.…”
Section: Methodsmentioning
confidence: 99%
“…The European Working Time Directive (EWTD) has made standards for weekly work hours for junior doctors to limit incidents at work [28]. To further limit junior doctors’ weekly work hours by simulation-based courses compensating for work hours seems unlikely and it would not increase the learning outcome after the EWTD has been implemented, as it has been shown that training outside of work during a trainee’s “personal time” does not minimize the effect of skill acquisition compared to training during work hours [29]. Lack of pay is not a deterrent for trainees who attend the courses using their personal time.…”
Section: Discussionmentioning
confidence: 99%